2010
DOI: 10.1074/jbc.m110.156703
|View full text |Cite
|
Sign up to set email alerts
|

The Necdin-Wnt Pathway Causes Epigenetic Peroxisome Proliferator-activated Receptor γ Repression in Hepatic Stellate Cells

Abstract: Hepatic stellate cells (HSCs), vitamin A-storing liver pericytes, undergo myofibroblastic trans-differentiation or "activation" to participate in liver wound healing. This cellular process involves loss of regulation by adipogenic transcription factors such as peroxisome proliferator-activated receptor ␥ (PPAR␥). Necdin, a melanoma antigen family protein, promotes neuronal and myogenic differentiation while inhibiting adipogenesis. The present study demonstrates that necdin is selectively expressed in HSCs amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 36 publications
6
40
0
Order By: Relevance
“…Immunofluorescence doublestaining of ACLP and β-catenin in these specimens demonstrated a significant increase in ACLP/β-catenin double-positive cells as compared with normal livers, and β-catenin was upregulated specifically in ACLP-positive cells in NASH ( Figure 3D and Supplemental Figure 13). As for the mRNA expression levels of Wnt1, Wnt3a, Wnt5a, and Wnt10b, which are reported to be correlated with the canonical WNT pathway in liver pathology (12,16,20,21), murine NAFLD livers and HSCs as well as human NAFLD liver samples demonstrated no changes when compared with their respective controls (Supplemental Figure 14). The above results indicated that in the progression of NASH, HSC-derived ACLP acts on HSCs themselves, thereby activating the HSCs and advancing liver fibrosis.…”
Section: Aclpmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunofluorescence doublestaining of ACLP and β-catenin in these specimens demonstrated a significant increase in ACLP/β-catenin double-positive cells as compared with normal livers, and β-catenin was upregulated specifically in ACLP-positive cells in NASH ( Figure 3D and Supplemental Figure 13). As for the mRNA expression levels of Wnt1, Wnt3a, Wnt5a, and Wnt10b, which are reported to be correlated with the canonical WNT pathway in liver pathology (12,16,20,21), murine NAFLD livers and HSCs as well as human NAFLD liver samples demonstrated no changes when compared with their respective controls (Supplemental Figure 14). The above results indicated that in the progression of NASH, HSC-derived ACLP acts on HSCs themselves, thereby activating the HSCs and advancing liver fibrosis.…”
Section: Aclpmentioning
confidence: 99%
“…Because ACLP/canonical WNT pathway activation triggered HSC activation, we examined this pathological mechanism further. It has been recently reported that activation of canonical WNT signaling represses PPARγ activity in HSCs, thereby promoting their activation (12,16). Therefore, we examined PPARγ activity upon the addition of rACLP to HSCs.…”
Section: Aclpmentioning
confidence: 99%
See 1 more Smart Citation
“…Necdin protein can prevent HSCs from developing adipogenic characters, while sustain the forming of myogenic characters which are favorable to the fibrogenesis (Tseng et al 2005;Zhu et al 2010). Canonical wingless-related MMTV integration site 10b (Wnt10b), downstream of necdin, has a "GN" box in its promoter.…”
Section: "Gn" Box In Wnt10b Gene Promoter Helps Ppar-γ Suppression Thmentioning
confidence: 99%
“…Interestingly, time course analysis of adipogenic markers shows that overexpression of necdin decreases their levels of expression. Necdin inhibition of adipogenic differentiation of pre-adipocytes has been previously described, 26,27 but no data are available on the co-factor that may cooperate with necdin in this process, and more experiments will be required to get more insight into this issue. There is evidence that in the aged or dystrophic muscle mesenchymal progenitors distinct from satellite cells contribute to ectopic fat cell formation in degenerating skeletal muscle, in aging or dystrophy.…”
Section: Discussionmentioning
confidence: 99%